Developing Prototype Integrated Reading Material For Junior High School - admin admin; Ninis Khoirotunnisa (DIDAKTIKA, 2017)
Reading skill is mainly acknowledged as the most important skill to be mastered. It is not only overemphasized for developing English skill but also critical understanding skills of students. Various factors have certainly contributed to this study. The lack of students’ interest became the main factor of the lowness of students reading skill. Besides the teaching material development required the balance of higher technology. This study aimed to optimize and accomplish the goal of learning reading which balance with the increasing of technology use as learning need nowadays by developing prototype integrated reading material for junior high school. To meet the objective of the study, the researcher used Research and Development as design of study involving need analysis, design, development, expert validation and try out. Questionnaire and interview were utilized as instrument in the field of need analysis. The result of development organized the prototype integrated reading material through PamanPinter-CALLs which developed in longtion auto run combining with adobe audition, hot potatoes, hangaroo, macromedia flash, and microsoft power point. It contained vocabulary corner, reading corner, audio corner, comprehension corner, and writing corner which covered pre-reading activity, whilst reading activity, and post reading activity. This was validated by three experts and tried out through students discussion and questionnaire. Finally the result might be utilized to help teachers and students in teaching learning reading using PC computer or smartphone. This prototype integrated reading material is able to employ in the home and in the class even individually or in group. So students can improve their reading skill autonomously by the guidance from the teachers before. Further, this program suggested to be developed in other any level. This program is more completed with speed reading correction to evaluate students speed reading and pronunciation correction to help students to have self-learning in pronunciation.